The excess air coefficient effect on the performances for a motorcycle twin-spark gasoline engine: A wide condition range study. (5th March 2019) - Deng, Banglin; Chen, Yangyang; Liu, Aodong; Xu, Zhengxin; Hu, Songyu; Fu, Jianqin; Liu, Xiaoqiang; Feng, Renhua; Zhou, Lili
Highlights: Performances of a twin-spark motorcycle engine were studied over a wide range condition. Thermal-work conversion is more efficient at lean mixtures benefitted from heat transfer and combustion efficiency. Combustion is more complete at lean side due to rich O2 and closer to TDC. From λ = 0.85 to 1.2 at 60% load HC and CO drop 20.5% and 1294.73%, NOx rises 66.7%. Engine knocking is effectively inhibited for different λs under dual spark operation. Abstract: The performance of motorcycles has a great influence on energy and environment due to the huge quantity. In this work we mainly explore the impact of air/fuel composition (λ) on engine torque, ECR (energy consumption rate), emissions and knocking of a twin-spark single cylinder motorcycle engine by experiment. The results illuminated that, the engine torque is smaller with the increase of λ. For example, at 60% engine load and 3000 rpm the engine torque decreases by 20.5% when the λ increased from 0.85 to 1.2. ECR becomes smaller as the λ increases, this phenomenon indicated that the thermal-work conversion is more efficient at lean operation. The CO and HC emissions decrease with the increase of λ. For instance, at 60% engine load, when λ increases from 0.85 to 1.2, while the CO decreases by 1294.73%. As expected, NO emission increases with the increase of λ, but further extension of λ does not deteriorate NO too much while gets lots benefits in CO emissions. In addition, the engine knocking is effectively inhibited for different λs under dual spark operation. Besides, the combustion process is also analyzed to explain the engine phenomenal performances.